2001
DOI: 10.1038/sj.onc.1204960
|View full text |Cite
|
Sign up to set email alerts
|

The HPV-16 E7 oncoprotein binds Skip and suppresses its transcriptional activity

Abstract: E7 is the major transforming protein of human papillomavirus (HPV), which is implicated in the development of cervical cancer. The transforming activity of E7 has been attributed in part to its interaction with the retinoblastoma (Rb) tumour suppressor; however, the Rb interaction alone is not su cient for transformation by E7. In a screen for cellular targets of HPV E7, we identi®ed the Ski interacting protein, Skip, as a new interacting partner of E7. We show that HPV-16 E7 associates with Skip via sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Lysis of cells and immunoblotting were carried out as described in ref. 36. mAbs 2-17 and EC10 were used to detect Src, and mAb4G10 (Upstate Biotechnology, Lake Placid, NY) was used to detect cellular phosphotyrosyl proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Lysis of cells and immunoblotting were carried out as described in ref. 36. mAbs 2-17 and EC10 were used to detect Src, and mAb4G10 (Upstate Biotechnology, Lake Placid, NY) was used to detect cellular phosphotyrosyl proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our results have added Skip-LEF-HDAC as one more Skip-mediated tripartite complex with three bipartite interactions, in addition to Skip-CBF1-NotchIC, Skip-CBF1-SMRT, Skip-VDR-RXR, and Skip-pRb-E7 (33,34,54,55). How Skip is involved dynamically in these conversion processes of Wnt signaling is not fully understood.…”
Section: Skip May Work As a Scaffold In ␤-Catenin-tcf-mediatedmentioning
confidence: 99%
“…E7 has been reported to bind to over 20 cellular proteins (2,8,11,47,55). These putative targets of E7 include multiple cell cycle regulators, such as the pocket proteins pRb, p107, and p130 and the cyclin-dependent kinase inhibitors p21 and p27 (47).…”
mentioning
confidence: 99%
“…These putative targets of E7 include multiple cell cycle regulators, such as the pocket proteins pRb, p107, and p130 and the cyclin-dependent kinase inhibitors p21 and p27 (47). Additional binding partners of E7 include transcription factors (c-Jun, IRF-1, and MPP2), transcriptional cofactors and chromatin-remodeling enzymes (TBP, TAF-110, Skip, p300, pCAF, and Mi2␤/histone deacetylase complexes), metabolic enzymes (M 2 pyruvate kinase and acid ␣-glucosidase), F-actin, and the proteasome (2,8,47,55). Thus, in vitro studies have suggested many possible mechanisms for E7 function.…”
mentioning
confidence: 99%